A study on oxidized-LDL cholesterol in normolipidemic retinal vein occlusion - Kapil Deb Lahiri; Gupta, Amit Kumar; Utpal Kumar Biswas (Asian Journal of Medical Sciences, 2023)
Background: Oxidized low-density lipoprotein (ox-LDL) has been implicated in atherosclerotic cardiovascular disease. Arteriolosclerosis is an important causative factor for retinal vein occlusion (RVO). Till, date there is dearth of literature on ox-LDL and RVO. Aims and Objectives: The objectives of this study were to see whether ox-LDL cholesterol is an independent risk factor in RVO with normal lipid profile. Materials and Methods: Lipid profiles and ox-LDL levels were assayed in 122 adult unilateral RVO cases and 142 age and sex matched controls in this 1 year old case–control study. Results: ox-LDL cholesterol levels were significantly elevated in RVO cases than controls (54.5±6.1 in cases vs. 36.6±5.6 in controls, P<0.01), although serum lipid profiles were normal in both cases and controls. Conclusion: The ox-LDL-induced atherosclerosis may be responsible for the retinal venous occlusion in absence of other risk factors. Hence, screening for ox-LDL in RVO patients should be worth considering especially in patients with normal lipid profiles.